IL-17 in lung disease: friend or foe?. Issue 8 (19th April 2013) - Tan, Hui-Leng; Rosenthal, Mark
Abstract : Interleukin 17 (IL-17) is a key proinflammatory cytokine in the T helper 17 pathway. While it is important in the clearance of certain pathogens, IL-17 has been shown to contribute to the pathogenesis of such inflammatory diseases as rheumatoid arthritis and psoriasis. In the lung, it has been postulated to be involved in the neutrophilic inflammation and airway remodelling of chronic respiratory conditions but the situation is increasingly complex. This review summarises the evidence for its role in several chronic inflammatory lung diseases: asthma, obliterative bronchiolitis, chronic obstructive pulmonary disease, sarcoidosis and cystic fibrosis.